Trimester-specific thyroid function markers and gestational diabetes risk: evidence from a tertile-based cohort of euthyroid pregnancies - Erkan Sağlam; Serenat Eris Yalçın; Mustafa Raşit Özler; Bekır Siddik Yılmaz; Nuray Nerez (The Journal of Maternal-Fetal & Neonatal Medicine)
Objective This study aimed to investigate whether thyroid-stimulating hormone (TSH), free triiodothyronine (fT3), free thyroxine (fT4), and the fT3/fT4 ratio—measured during the first and second trimesters—are associated with the development of gestational diabetes mellitus (GDM) in euthyroid pregnant women. Their predictive value was evaluated using tertile-based logistic regression.Materials and Methods In this retrospective cohort study, 200 euthyroid pregnant women without thyroid disease or treatment history were included. GDM was diagnosed according to the International Association of Diabetes and Pregnancy Study Groups (IADPSG) criteria. Thyroid parameters were measured in the first (9–14 weeks) and second (22–28 weeks) trimesters. Tertile-based univariate and multivariate logistic regression analyses were conducted, adjusting for maternal age, BMI, smoking, and family history of diabetes.Results Women in the highest tertile (tertile 3) of first-trimester fT3 (>3.61 pg/mL) and fT3/fT4 ratio (>0.27) had a significantly increased risk of GDM (adjusted OR = 9.72 and 4.05, respectively; p < 0.001). Conversely, being in the highest tertile of TSH (tertile 3 > 2.34 µIU/mL) during both trimesters was associated with a significantly lower risk of GDM (OR = 0.32–0.04; p < 0.001). TSH levels increased, while fT3 and fT4 levels decreased significantly across trimesters (p < 0.001). GDM was associated with lower gestational age at delivery (p < 0.001), increased NICU admission (p = 0.041), and a modest positive correlation between first-trimester fT3/fT4 ratio and birth weight (r = 0.15; p = 0.034).Conclusion Being in the highest tertiles of fT3 and fT3/fT4 ratio during the first trimester—despite remaining within the euthyroid range—was linked to elevated GDM risk. In contrast, the highest TSH tertiles in both trimesters were associated with a decreased risk. These findings suggest that even subtle thyroid hormone variations within normal limits may influence glucose metabolism and support the utility of early thyroid function evaluation for predicting gestational metabolic risk.